Assessment and apply of an enhanced exergy analysis for an argon liquefaction system. (2nd February 2021) - Karabuga, Arif; Utlu, Zafer
Argon basically and widely liquefied by three different liquefaction methods such as cryogenic, pressure swing adsorption, and membrane. The cryogenic method with the highest purity rate constitutes the method of this study. In the present work, conventional and enhanced exergy analyses were applied to the liquefaction process of argon. In the enhanced exergy analysis, splitting the exergy destruction into endogenous/exogenous and avoidable/unavoidable parts represents a new direction. In the study, forward exergy analysis is performed for each component and endogenous, exogenous, unavoidable, and avoidable values of these components were calculated. When the convectional exergy analysis is examined, the exergy efficiency of the argon liquefaction system is calculated as 51.77%. When the enhanced exergy analysis of the system is examined, it is found that the highest exergy destruction occurred in the turbine as 614.3 kW. Furthermore, the highest endogenous exergy destruction was found as 494 kW (80.4%) in the turbine.